IMPACT OF A REHABILITATION PROGRAM ON THE URINARY MANAGEMENT OF PATIENTS AFFECTED BY CEREBROVASCULAR ACCIDENT - Chiado,Andreia Patrícia Azevedo (2022)
ABSTRACT Objective: to assess the effect of a Nursing Rehabilitation program on the urinary incontinence management of women after a CVA. Method: quantitative, quasi-experimental, and longitudinal study conducted in a convalescence unit in the Viana do Castelo district, Portugal, between September 2018 and March 2019. The sample included women (n=30) aged between 45 and 90, experiencing urinary incontinence after a CVA, assigned to two groups: experimental group (n=15) and control group (n=15). The functional rehabilitation program was applied to the experimental group for 4 weeks. The program comprises behavioral changes and an exercise plan to strengthen pelvic floor muscles, and the impact of urinary incontinence was assessed before and after the intervention. Results: a statistically significant correlation was found between the level of functional disability and the impact of urinary incontinence (r=-0.499; p=0.005). Hence, the level of functional disability influences the impact of urinary incontinence on quality of life. The functional rehabilitation program implemented in the experimental group obtained positive results and decreased the frequency (t=6.985, p=0.000) and amount (Z=-2.762, p=0.006) of urine loss. Conclusion: the functional rehabilitation program positively impacted and decreased the frequency and amount of urine loss.